Carbohidrate Distribution In The Small Intestine of Sumba Ongole Cattle (Bos indicus) - Filphin Adolfin Amalo; Inggrid Trinidad Maha; Yulfia N. Selan; Jeanet F. T. Lali Pora; Nila Sari Ngadi (JURNAL ILMIAH PETERNAKAN TERPADU, 2022)
The small intestine has cells that function to secrete mucus that protects the intestine from pathogenic agents and mechanical damage. One of the components of mucus is carbohydrates. This study aims to knowing the distribution of acidic and neutral carbohydrates in the small intestine of sumba ongole (Bos indicus) cattle. Six samples of the small intestine were collected from East Sumba Slaughter House. The tissue was fixed in formalin 10 %, continued with processed histologically and AB-PAS staining. The results showed that acidic and neutral carbohydrates were distributed in the tunica of the duodenum, jejunum, and ileum with varying intensity. The strong intensity was seen in goblet cells, Lieberkuhn crypts, and Brunner's glands. The different distribution of carbohydrates in the small intestine is related to the mucus secretion of each cell and that function.